La producción de masculinidad : entre la dominación y el rechazo de lo femenino (2008)
ABSTRACT: The question regarding the construction of masculinity has been debated by the different disciplines including anthropology which has discussed how it, masculinity, is adjudicated and assumed out of complex rites of passage. The interest of this article is to compare the distinct historical and cultural representations that attempt to respond to this question, at the same time that is proposes the hypothesis that the constitution of masculinity is based on a rejection of the feminine that is reproduced on different social, political, and psychic planes, in which lies the idea that there exists a dominant masculinity over the feminine, but which in a paradoxical manner disguises the masculine desire for the feminine.